High thermoelectric power factor of Sr doped Bi2Te3 thin film through energy filtering effect. (April 2023) - Ashfaq, Arslan; Sabugaa, Michael M.; Moussa, Mongi Ben; Almousa, N.; Shokralla, Elsammani Ali; Capangpangan, Rey Y.; Alguno, Arnold C.; Hossain, Md Amzad; Alanazi, Abdulaziz M.; Abboud, Mohamed
Abstract: The conventional Bi2 Te3 thin film can be used for thermoelectric power factor. However, the poor efficiency of Bi2 Te3 thin film severely limits its wide range of applications. In this study, we have reported the Sr doped Bi2 Te3 thin film coated on a glass substrate via a simple thermal evaporation route. The synthesized thin films have been post-annealed at a temperature (773 K) in the tube furnace for 30 min. The x-ray diffraction data confirmed that the planes of the pure and Sr doped Bi2 Te3 thin film and also studied the effect on the parameters of the crystal. The surface morphology of the pure and Sr doped Bi2 Te3 thin film samples has been studied via a scanning electron microscope. The highly intact grains with no porosity and uniformly oriented granular surface morphology have been observed. The grain size of the synthesized samples decreases with increasing the Sr content in the Bi2 Te3 matrix. We have reported the enhancement of the Seebeck coefficient and electrical conductivity. These factors control the grain size and density with the doping concentration. The Seebeck coefficient enhancement has up to 91 μV/ o C due to the energy filtering effect at the small grain boundaries. The electrical conductivity increases with increasing the charge carrier concentration and decreasing grain size, making the small domain more conductive. As a result, the film with a small grain size exhibited a maximum room temperature power factor of 15.61 μWcm −1  K −2 . This work demonstrates that thermal evaporation is an effective approach for synthesizing the Sr doped Bi2 Te3 thin films.